Teaching Common Core Math Practices to Students with Disabilities - Stephan, Michelle; Smith, Jennifer (Journal of the American Academy of Special Education Professionals, 2012)
The widespread adoption of the Common Core State Standards (2010) has caused mathematics and special educators to reconsider instructional methods. The Common Core introduces eight Standards for Mathematical Practice that outlines the dispositions that should be fostered in students. Most notable are those that push students to analyze problems, create a solution, explain/prove their reasoning to others and critique other students’ methods. Although direct instruction has been the primary approach advocated in working with students who have disabilities, this approach tends to teach basic skill proficiency with less emphasis on the problem solving advocated in the Common Core. In this paper, we use examples from our own teaching to offer an alternative to direct instruction for special education teachers who are moving into mathematics or co-teaching, an approach that has the potential for fostering the disposition advocated in the Common Core State Standards.